Dynamic mechanical response of polyetheretherketone (PEEK) exposed to cyclic loads in the high stress tensile regime. (November 2015) - Berer, M.; Tscharnuter, D.; Pinter, G.
Abstract : Graphical abstract: Highlights: Tensile fatigue tests of polyetheretherketone at high load levels. Separation of storage and loss parts (viscoelastic analysis). Calculation of dissipation energy rate. Significant change of mechanical properties during tests. Hypothesis for mechanism of material change. Abstract: Tensile fatigue tests of PEEK at high load levels were carried out and analyzed regarding the dynamic mechanic behavior of the material during the tests. The experiments were conducted in the high stress tensile regime of PEEK. After a short period of unsteady temperature increase distinct material changes were observed during the tests at medium and high load levels. The storage modulus increased continuously while the loss modulus, loss factor (tan δ ) and the dissipation energy rate decreased continuously. It was concluded that the accumulation of residual stresses because of partially irreversible deformation causes this effect.